2020
DOI: 10.1111/jori.12313
|View full text |Cite
|
Sign up to set email alerts
|

Annuitization and aggregate mortality risk

Abstract: It is well established that annuities can fully diversify idiosyncratic mortality risks. However, survival rates at the cohort level are changing, raising the question what is the scope of annuities in the presence of aggregate mortality risk? In an overlapping generations setting, we show that risk free annuities exist, but offer a return below the (fair) certainty equivalent return, and agents do not fully annuitize their savings. Higher aggregate mortality risk increases savings and thus the mean level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Therefore, we choose the exponential function, which also maintains the monotonicity property to guarantee the ease of interpretation. We express α, β, and ϛ as in ( 3), (4), and (5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we choose the exponential function, which also maintains the monotonicity property to guarantee the ease of interpretation. We express α, β, and ϛ as in ( 3), (4), and (5).…”
Section: Methodsmentioning
confidence: 99%
“…Second, some parties may consider that overall degrees of freedom is smaller than pooling both sexes into a model. Therefore, we construct the pooled model by modifying (3), (4), and (5). Assuming that the estimate of trend parameters are equal for both males and females, our expressions for the value of α, β, and ϛ in the pooled model are expressed as ( 9), (10), and (11) with adding a sex indicator denoted by s, with the value of 1 for males and 0 for females.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors quantified the importance of cohort mortality risk using the Lee and Carter (1992) model and then assessed its consequences on the money's worth (MW) distribution of annuity values. In relation, recent theoretical study by Andersen and Gestsson (2021) showed that aggregate mortality risk affects the scope for annuitization in that agents do not fully annuitize their savings in an overlapping generations setting, which underscores the role of aggregate mortality risk in annuity markets.…”
Section: Introductionmentioning
confidence: 98%